Risk Groups of Developing Active Tuberculosis in Liver Transplant Recipients in a Tuberculosis Endemic Area: Risk Stratification by Chest Image and Interferon Gamma Release Assay. (December 2021) - Kim, Si-Ho; Oh, Suhyun; Nham, Eliel; Ko, Jae-Hoon; Huh, Kyungmin; Cho, Sun Young; Kang, Cheol-In; Chung, Doo Ryeon; Choi, Gyu-Seong; Kim, Jong Man; Joh, Jae-Won; Peck, Kyong Ran
Highlights: We analyzed factors that may predict active TB in liver transplantation recipients. IGRA positivity itself was not associated with TB development in a TB-endemic area. IGRA positive predicted active TB when chest images suggested a previous TB infection. Both IGRA and chest CT should be considered to identify LTBI treatment candidates. Abstract: Objectives: We implemented a stratified risk analysis to predict the development of active tuberculosis (TB) in liver transplantation (LT) recipients based on IGRA and chest images in a TB-endemic area. Methods: In this retrospective cohort study, LT recipients who tested for IGRA between May 2008 and December 2017 were included. Chest images compatible with old TB lesions were considered as positive images. LT recipients were divided into six groups: LT recipients with history of treated TB, image (+)/IGRA (+), image (+)/IGRA (-), image (-)/IGRA (+), image (-)/IGRA (-) and LTBI treated. The Cox regression model was used to analyze risk groups. Results: Among the 717 eligible LT recipients included in this study, 21 patients developed active TB. Incidence rates of TB were 2, 261, 724, and 119 cases/100, 000 person-years in the 1st, 2nd, and ≥ 3rd year after transplantation, respectively. History of treated TB (HR 18.92; 95% CI 4.10–87.25) and image (+)/IGRA (+) (HR 10.86; 95% CI 2.75–42.89) were independent risk factors for developing active TB. IGRA (+) with a negative image was not a risk factor. Conclusions: Our findings suggested that both IGRA and chest images should be considered to identify risk groups for LTBI treatment.